2021
DOI: 10.1038/s41590-020-00857-2
|View full text |Cite
|
Sign up to set email alerts
|

Naturalizing mouse models for immunology

Abstract: s we have seen vividly in 2020-2021, infectious diseases pose perennial challenges to human health around the globe. Preclinical animal models, usually starting with experiments on 'the laboratory mouse' , enable researchers to reveal extraordinary details of how the immune systems of mammals respond to such challenges. Many immune mechanisms elucidated in lab mice also hold in people and inform the design of clinical therapies. Indeed, lab mice can arguably serve as models for both mammalian immune function i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 83 publications
(134 reference statements)
1
72
0
Order By: Relevance
“…Recent paradigm-shifting work illustrated that lab mice are too far removed from natural environmental conditions to reliably mirror the physiology of free-living mammals like humans (212)(213)(214)(215). This circumstance distorts how the immune system of ultra-clean lab mice develops and functions, leading to false assumptions of how the human immune system works as reviewed elsewhere (216,217). To address these shortcomings several approaches have been suggested: Cohousing of lab mice with pet store mice (212), sequential infections of lab mice (213), rewilding of lab mice in semi-natural habitats (214), engraftment of wild mouse gut microbiota into lab mice (215) and the transfers of lab mouse embryos into wild mouse surrogate mothers, the so-called "wildling" model (218).…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Recent paradigm-shifting work illustrated that lab mice are too far removed from natural environmental conditions to reliably mirror the physiology of free-living mammals like humans (212)(213)(214)(215). This circumstance distorts how the immune system of ultra-clean lab mice develops and functions, leading to false assumptions of how the human immune system works as reviewed elsewhere (216,217). To address these shortcomings several approaches have been suggested: Cohousing of lab mice with pet store mice (212), sequential infections of lab mice (213), rewilding of lab mice in semi-natural habitats (214), engraftment of wild mouse gut microbiota into lab mice (215) and the transfers of lab mouse embryos into wild mouse surrogate mothers, the so-called "wildling" model (218).…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…‘Germ free’ murine models are also potentially an attractive option for modeling UTI and the gut microbiota/UTI axis, allowing exclusive colonization of certain pathogens or purposefully introduced commensal species. For immunological purposes, naturalizing mouse models can also be used to help translate research to humans ( Graham, 2021 ). The immune profiles of laboratory mice are different from that of human as they have a low density of mature T cells ( Beura et al., 2016 ) and lower LPS sensitivity which could lead to differences in pathogenesis and treatment responses in humans ( Graham, 2021 ).…”
Section: Animal Models For Studying Utimentioning
confidence: 99%
“…For immunological purposes, naturalizing mouse models can also be used to help translate research to humans ( Graham, 2021 ). The immune profiles of laboratory mice are different from that of human as they have a low density of mature T cells ( Beura et al., 2016 ) and lower LPS sensitivity which could lead to differences in pathogenesis and treatment responses in humans ( Graham, 2021 ). However, germ-free mice are more expensive and need specialized equipment and training ( Kennedy et al., 2018 ).…”
Section: Animal Models For Studying Utimentioning
confidence: 99%
“…Therefore, the group showed that the microbiota of wild animals excellently phenocopied human immune responses and that the reproducibility of preclinical studies could be enhanced using a model composed of natural microbiota and certain pathogens [ 252 ]. An excellent review on the effect of “naturalizing mouse models”, which of course goes well beyond the microbiome as it includes biotic and abiotic factors, has recently been published by Graham [ 253 ].…”
Section: How To Ensure Validitymentioning
confidence: 99%